Immunogenicity of a single 4CMenB vaccine booster in adolescents 11 years after childhood immunisation. Issue 32 (30th July 2022) - Rollier, Christine S.; Dold, Christina; Blackwell, Luke; Linder, Aline; Silva-Reyes, Laura; Clutterbuck, Elizabeth; Davis, Kimberly; Ford, Karen; Liu, Xinxue; Holland, Ann; Chan, Hannah; Harbinson, Holly; et al.
Highlights: Two doses of 4CMenB are required in naïve adolescents to elicit sufficient bactericidal activity. Impact of childhood vaccination with 4CMenB on response to a single boost at adolescence is unknown. No safety concerns raised after administration of fourth to sixth doses of 4CMenB in adolescence. A single dose induced better responses in previously vaccinated than in naïve adolescents. Responses to the adolescent dose were better when a preschool boost had been administered. Abstract: The clinical development of the meningococcal vaccine, 4CMenB, included 2 doses in vaccine-naïve adolescents, which was considered unlikely to be cost-effective for implementation. Theoretically, priming with 4CMenB in early childhood might drive strong immune responses after only a single booster dose in adolescents and reduce programmatic costs. To address this question, children over 11 years old who took part in previous trials involving the administration of 3–5 doses of 4CMenB at infant/preschool age from 2006 were recruited into a post licensure single-centre trial, and were divided into two groups: those who received their last dose at 12 months old (infant group) and those who received their last dose at 3 years old (infant + preschool group). Naïve age-matched controls were randomised to receive one (adolescent 1 group) or two doses at days 0 and 28 (adolescent 2 group) of 4CMenB. Serum bactericidal antibody (SBA) assays using human complement were performed against three reference strains prior to vaccination, and at 1, 6 and 12 months. Previous vaccination was associated with a higher response to a single booster dose at 11 years of age, one-month post-vaccination, when compared with a single dose in naïve age-matched controls. At day 180, the highest responses were observed in participants in the infant + preschool group against strain 5/99 (GMT 316.1 [CI 158.4 to 630.8]), as compared with naïve adolescents who received two doses (GMTs 84.5 [CI 57.7 to 123.6]). When the last dose was received at 12-months of age, responses to a single adolescent dose were not as robust (GMT 61.1 [CI 14.8 to 252.4] to strain 5/99). This descriptive study indicates that the highest SBA responses after a single dose in adolescence were observed in participants who received a preschool dose, suggesting that B cell memory responses are not sufficiently primed at less than 12 months of age. Trial registration EudraCT 2017-004732-11, ISRCTN16774163.